Shewanella oneidensis MR-1 nanowires are outer membrane and periplasmic extensions of the extracellular electron transport components - Pirbadian, Sahand (National Academy of Sciences, 2014)
Bacterial nanowires offer an extracellular electron transport (EET) pathway for linking the respiratory chain of bacteria to external surfaces, including oxidized metals in the environment and engineered electrodes in renewable energy devices. Despite the global, environmental, and technological consequences of this biotic–abiotic interaction, the composition, physiological relevance, and electron transport mechanisms of bacterial nanowires remain unclear. We report, to our knowledge, the first in vivo observations of the formation and respiratory impact of nanowires in the model metal-reducing microbe Shewanella oneidensis MR-1. Live fluorescence measurements, immunolabeling, and quantitative gene expression analysis point to S. oneidensis MR-1 nanowires as extensions of the outer membrane and periplasm that include the multiheme cytochromes responsible for EET, rather than pilin-based structures as previously thought. These membrane extensions are associated with outer membrane vesicles, structures ubiquitous in Gram-negative bacteria, and are consistent with bacterial nanowires that mediate long-range EET by the previously proposed multistep redox hopping mechanism. Redox-functionalized membrane and vesicular extensions may represent a general microbial strategy for electron transport and energy distribution.